2019
DOI: 10.1111/pedi.12815
|View full text |Cite
|
Sign up to set email alerts
|

Online education for gluten‐free diet teaching: Development and usability testing of an e‐learning module for children with concurrent celiac disease and type 1 diabetes

Abstract: Background and Objective Celiac disease (CD), the most common genetically‐based food intolerance, affects 3% to 16% of children with type 1 diabetes (T1D). Treatment involves lifelong adherence to a gluten‐free diet (GFD). Individualized dietary education is resource‐intensive. We, therefore, sought to develop and test the usability of an e‐learning module aimed at educating patients and caregivers regarding implementation of the GFD in children with concurrent CD and T1D. Methods An interactive e‐learning mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 56 publications
(105 reference statements)
3
36
0
1
Order By: Relevance
“…Use of unexplained medical jargon with families and patients is still common in the paediatric field [17] although it has been shown that information, which can be processed fluently, is considered more trustworthy, honest and safe and that the recipient is more inclined and likely to fulfil inferred tasks [5]. Processing fluency depends mainly on perceptive fluency, determined by visual display and linguistic fluency, which depends on wording and grammatical complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of unexplained medical jargon with families and patients is still common in the paediatric field [17] although it has been shown that information, which can be processed fluently, is considered more trustworthy, honest and safe and that the recipient is more inclined and likely to fulfil inferred tasks [5]. Processing fluency depends mainly on perceptive fluency, determined by visual display and linguistic fluency, which depends on wording and grammatical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in patients with chronic diseases effective health education does not only improve knowledge, but also supports adherence to treatment and successful self-management, by influencing the patients’ attitude and daily practice [17, 18]. All these factors are essential for optimal outcome in patients with IEM [5, 7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed-methods feasibility testing approach will be used with iterative cycles of testing the developed intervention. 25,26 A satisfaction scale, semi-structured interview, feasibility and observation checklist will be used to assess the feasibility and usability of the education module in real-world settings.…”
Section: Feasibility Evaluation: Mixed-methods Studymentioning
confidence: 99%
“…So, different methods were studied to overcome these limitations. In this regard, various online education programs have been designed and applied in the adult 4 and children celiac patients 5 and their positive effect has been reported. However, this method needs internet access.…”
Section: Introductionmentioning
confidence: 99%